205k views
3 votes
If k(x)=x²-4 find k(2x)


1 -4
2-x²
3-2x²-4
4-4x²-4


User Fantasim
by
5.8k points

1 Answer

2 votes

Answer:

4. 4x² - 4

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation
  • Combining Like Terms

Explanation:

Step 1: Define

k(x) = x² - 4

k(2x) is x = 2x

Step 2: Evaluate

  1. Substitute in x: k(2x) = (2x)² - 4
  2. Exponents: k(2x) = 4x² - 4
User PierreN
by
6.5k points